Multicast-unicast key management and data delivery method in wireless IPv6 networks - Zare Anari, Abbas Mehdizadeh (2012)
Multicast is an efficient way of transmitting data simultaneously to a group of users. It has the advantage of reducing the required bandwidth of data delivery compared to unicast transmission. Nevertheless, existing multicast method suffers from several major drawbacks which can be viewed from two different viewpoints, namely,security and Quality of Service (QoS). In regard to security, the main challenge is to provide security protection to data which are multicast to many users. This can be achieved by using a secure key management process, specifically by increasing the level of encryption/decryption of transmitted data. Whenever a new node is granted to join or leave a multicast group, a new key should be generated and distributed to every node in the network. Considering a highly dense environment where connection of users to the network is frequently changing due to join or leave operations, such approach may burden a network device with a huge amount of complex encryption and decryption process. While a number of algorithms has been proposed to address this issue, most of the existing approaches have to increase their encryption and decryption cycles in order to maintain the security level of the key management, thereby again suffering from high computation cost. Meanwhile, from the QoS perspective, multicast over Wireless Local Area Networks (WLANs) offers a trade-off between data transmission rate and coverage. The larger the coverage is, the lower the transmission rate would be. Unfortunately, the transmission rate of existing multicast is confined by the user with the lowest data rate in the group, also known as fixed base rate problem. In this thesis, the aforementioned issues are addressed extensively in a new and efficient way. Instead of focusing on either security or QoS, this research highlights the possibility of addressing both criteria without having to sacrifice one for the sake of the other. By focusing mainly on Internet Protocol version 6 (IPv6) wireless networks, the use of both multicast and unicast transmissions for multicast service are considered. By integrating both multicast and unicast methods, it is envisaged that the proposed solution inherits their monumental advantages, and therefore is able to facilitate a lightweight key management process to multicast IPv6 as well as addressing the fixed base rate problem of multicast transmission. Moreover, this thesis places emphasises more on the IPv6 multicast transmission instead of the conventional Internet Protocol version 4 (IPv4). The feasibility and performance of the proposed key management method is evaluated analytically and empirically (in an IPv6 test-bed environment), as well as is analyzed based on Markov Chain and Poisson Arrival Process. The results are compared with existing key management methods in terms of communication, computation, and storage costs. The performance evaluation indicates the efficiency of the proposed scheme in reducing such costs, while at the same time maintaining both forward and backward securities. The overall improvements of communication, computation, and storage costs are more than 64%, 19%, and 29%,respectively. For evaluation of the proposed data delivery method, the proposed method is implemented in indoor and outdoor environments and the results are compared to the conventional multicast method. The transmission of real-time video application is considered in the test-bed. The proposed method is able to improve the throughput and video quality experienced by end user, with low packet loss and transmission delay. The average improvements are 65%, 48.3%, 67.3%, 47.9%, and 66% for throughput, packet loss, packet delay, end-to-end delay, and jitter, respectively.